The impact of health information exchange on healthcare quality and cost-effectiveness: A systematic literature review. (July 2018) - Sadoughi, Farahnaz; Nasiri, Somayeh; Ahmadi, Hossein
Abstract : A review regarding the impact of HIE on healthcare quality and cost-effectiveness is conducted. Findings suggest positive financial and quality impact related to HIE use in healthcare. There are lack of robust studies demonstrating the impact of HIE on cost and quality of care. Further high quality researches are needed to provide a better understanding of the domain of HIE impact and to increase users' participation and motivation for successfully adopting HIE technology. Abstract: Background and Objective: Health Information Exchange (HIE) is known as a technology that electronically shares all clinical and administrative data throughout healthcare settings. Despite this technology has a great potential in the healthcare industry, there is a limited and sparse evidence of articles which illustrated the impact of HIE on quality of care and cost-effectiveness. This work presents a systematic review that evaluates the impact of HIE on quality and cost-effectiveness, and the rates of HIE adoption and participation in healthcare organizations. Methods: We systematically searched all English papers that were indexed in four major databases (Science Direct, PubMed, IEEE and Web of Science) between 2005 and 2016. Consequently, 32 identified papers appeared in 21 international journals and conferences. Eligible studies independently were critically appraised, collected within data extraction form and then thematically analyzed by two reviewers and if necessary, the third author. The selected papers have been classified based on 11 main categories including publication year, journal and conference names, country and study design, types of data exchanged, healthcare levels, disease or disorder, participants in organizations and individuals, settings characteristics and HIE types, the impact of HIE on quality and cost-effectiveness, and the rates of HIE adoption and participation. Results: Of the 32 articles, 25 studies investigated the financial and clinical impact of HIE. Overwhelmingly, HIE studies have reported positive findings for quality and cost-effectiveness of care. 15 of HIE studies (60%) demonstrated positive financial effects and 16 studies (64%) reported positive effects on quality improvement of patient care. However, the overall quality of the evidences was low. In this regard, cohort study (59.38%) was the most common used study design. Nine studies presented the rates of HIE adoption and participation. The lowest and highest participation rates were 15.7% and 79%, respectively. Conclusions: HIE can be considered as a superior potential for healthcare information system, resulting to promote patient care quality and reduce costs related to resource utilization. However, further researches are needed in order to provide a better understanding of this domain and accordingly attain new opportunities to increase users' participation and motivation for successfully adopting this technology.